Contribution of Interleukin-17A to Retinal Degenerative Diseases - Zhong, Huimin; Sun, Xiaodong (Frontiers in Immunology, 2022)
Retinal degenerative diseases are a leading cause of vision loss and blindness throughout the world, characterized by chronic and progressive loss of neurons and/or myelin. One of the common features of retinal degenerative diseases and central neurodegenerative diseases is chronic neuroinflammation. Interleukin-17A (IL-17A) is the cytokine most closely related to disease in its family. Accumulating evidence suggests that IL-17A plays a key role in human retinal degenerative diseases, including age-related macular degeneration, diabetic retinopathy and glaucoma. This review aims to provide an overview of the role of IL-17A participating in the pathogenesis of retinal degenerative diseases, which may open new avenues for potential therapeutic interventions.